Pengaruh Penerapan Teknologi Big Data dan Independensi Auditor terhadap Efektivitas Proses Audit - Indi Rakhmawati; Nabila Nur Maulida; Dien Noviany Rahmatika (Jurnal Kendali Akuntansi, 2024)
Research Objectives: This study aims to review and re-analyze the information that has been in previous studies because Big Data Technology in Indonesia is still in the development stage and has become a hot topic in Indonesia. Auditor independence is defined as a mental attitude that is free from influence, not controlled by other parties and not dependent on others. This proves that auditor independence plays an important role in an organization and builds accountability in the organization. The author hopes that this research can be the basis and provide ideas for new research in the future. Research Method: This study was conducted using the SLR (Systematic Literature Review) method with a total of 28 previous journals taken that were analyzed in this study Research Results: The results of the study show that the integration of Big Data technology substantially affects the